ANALISA KOMPARASI DAYA DUKUNG PONDASI BORED PILE SECARA ANALISTIS TERHADAP HASIL LOADING TEST STUDI KASUS PROYEK PEMBANGUNAN REZ HOTEL - Savira Mirda Anggraeni; Hartopo Hartopo; Totok Apriyanto (Jurnal Teknik Indonesia, 2022)
Foundation failure and other factors that can cause bearing capacity to be incompatible when in the field. This is one of the factors that encourage direct loading tests in the field. Main objective of this study is to s to calculate and compare the ultimate bearing capacity of drilled pile after implementation with ultimate bearing capacity at the time of planning. SPT results were calculated using the Aoki Velosso method, the Decourt method, and the Reese & Wright method. Based on the calculation of the carrying capacity that has been carried out, there are differences in results, both due to the use of the method and the location of the point being reviewed. Based on the SPT data obtained from the calculation results of each Aoki Velosso method for TP-1/BP.48 the value of Qu = 783,933 tons while for TP-3/BP.78 the value of Qu = 1301,239, the Decont method for TP-1/BP.48 values Qu = 2593.098 tons while for TP-3/BP.78 the value of Qu = 2091.817, the Reese & Wright method for TP-1/BP.48 the value of Qu = 401.030ton while for TP-3/BP.78 the value of Qu = 334.022 and the results The loading test of the two test piles is TP-1/BP.48 Qu = 256 tons and TP-3/BP.78 Qu = 257 tons. Based on the calculation results, it can be seen that the efficient method used is the Reese & Wright method because the results of the calculation method are the smallest results, this is necessary to maintain building safety.